Evaluating the LEAP experience using a contextually oriented model - Jacobs, Cecilia (Cape Technikon, 1998)
This study presents a model for the evaluation of educational innovation in a context of transformation. The model incorporates formative, summative and illuminative evaluation goals and emphasises the need to locate the innovation which is being evaluated within the context and policy framework of its operation. The evaluation framework provided by the model takes into account the full range of variables impacting on innovative educational practice and subjects the innovation, along with its transforming educational context, to the scrutiny of evaluation. The ten-stage generalised evaluation model is presented as a framework for the evaluation of any type of educational innovation. In this study the model is applied to the evaluation of an innovative intervention, LEAP (Learning in English for Academic Purposes), at a tertiary institution in South Africa. The LEAP course aims to develop English academic literacy skills in students, foster student-centred learning and teaching and promote the transfer of academic literacy skills across the curriculum. The background to, theoretical underpinnings and development of the course are expanded on in the study. In line with the model, the LEAP intervention is located within the context and policy framework of its academic context. The principal stakeholders in the LEAP intervention are identified. They are used as sources to identify the aspects of LEAP to be evaluated, as well as to identify the criteria for evaluation. An eclectic approach is adopted in the evaluation of the LEAP course. Both quantitative and qualitative data collection methods are employed, using a variety of instruments. A range of sources is consulted to cross-validate the analysis of the data, and recommendations are made on the basis of conclusions drawn from the interpretation of the data. The final section of the study reflects on the whole evaluation process and areas for further research are also discussed.
Thesis (MTech(Education))--Cape Technikon, 1998
Keywords: English language -- Problems, exercises, etc; Achievement tests -- South Africa